S17-2: Physical Education for a Sustainable Future: Merging Health Promotion Through Physical Literacy With Global Environmental Responsibility (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This study explores how the integration of holistic health frameworks (One Health, EcoHealth, and Planetary Health) can reshape the mission of physical education (PE) by aligning it with both health promotion and environmental responsibility. In doing so, it redefines physical literacy (PL) as a foundation for developing sustainable, active lifestyles within ecological limits.Methods: A critical narrative synthesis of interdisciplinary literature, policy documents (e.g. UNESCO, World Health Organization), and educational models was conducted to examine the intersections between physical literacy, health education, and sustainable development. Secondly, an analysis of conceptual shifts in the definition of health and their influence on PE’s pedagogical goals and practices was carried out, using comparative matrices to identify the impacts of the three health frameworks on the four dimensions of PL: physical, cognitive, psychological, and social.Results: Our findings show that reorienting PE through Planetary Health promotes physical activities that reduce carbon emissions and raise awareness of planetary boundaries. EcoHealth emphasises embodied and empathetic connections to ecosystems through nature-based activities and community engagement, while One Health prioritises cross-sectoral health practices to prevent zoonotic diseases. Each model reconfigures the development of PL by embedding health education within environmental and social systems thinking, offering distinct yet complementary pedagogical strategies. The article also presents real-world examples (e.g. mountain biking in deprived areas) that operationalise these theoretical models, illustrating the feasibility of PE interventions grounded in PL for sustainability.Conclusions: A reconceptualisation of health in PE, one that acknowledges ecological interdependence, is necessary to address the intertwined crises of physical inactivity and environmental degradation. PL offers a unifying, adaptable framework through which PE can contribute meaningfully to holistic health and sustainability. Adopting context-sensitive health models in PE supports the development of environmentally aware, physically literate citizens committed to active and sustainable lifestyles.Support/Funding Source: This research received no external funding from commercial or not-for-profit sectors.Keywords: Physical literacy, health education, sustainability, planetary health, physical education